2022
DOI: 10.3390/antiox12010065
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antioxidant Properties and Metabolite Profiling of Acer pseudoplatanus Leaves of Different Colors

Abstract: Acer pseudoplatanus (maple) is a widely grown ornamental plant. In addition to its ornamental and ecological value, it also has potentially high economic value. It is a rich source of polyphenols and exhibits antioxidant activity. However, the relationship between polyphenol content and antioxidant activity in maple leaves of different colors (green, yellow, and red) has not yet been investigated. In this study, the total polyphenol (TP), total flavonoid (TFlav), tannin (TET), chlorophyll a and b (Chl a and b)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 93 publications
0
2
0
1
Order By: Relevance
“…The chlorophyll content was determined by using the methods previously described by Wang, H. et al and Zhang, M. et al, and the carotenoid content was determined by using the protocol reported by Samec, D. et al [ 53 , 54 , 55 ]. The content of the pigments was calculated based on the measured absorbance value, the solution volume, and the sample mass according to the following equations: where V is the volume of the extract (mL); m is the weight of the dry sample (mg); and A_663.2, A_646.8, and A_452.5 are the absorbance values of the mixture solution at 663.2, 646.8, and 452.5 nm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The chlorophyll content was determined by using the methods previously described by Wang, H. et al and Zhang, M. et al, and the carotenoid content was determined by using the protocol reported by Samec, D. et al [ 53 , 54 , 55 ]. The content of the pigments was calculated based on the measured absorbance value, the solution volume, and the sample mass according to the following equations: where V is the volume of the extract (mL); m is the weight of the dry sample (mg); and A_663.2, A_646.8, and A_452.5 are the absorbance values of the mixture solution at 663.2, 646.8, and 452.5 nm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Hal ini terlihat dari aktivitas antioksidan ekstrak daun tenggulun tua yang lebih rendah dari ekstrak daun tenggulun dewasa. Zhang et al (2023)…”
Section: Aktivitas Antioksidanunclassified
“…Flavonoids, phenolic acids, and saponins are distributed in all legume plants, whereas carotenoids, anthocyanins, and alkaloids are not present in all legume plants, and these substances are closely related to the antioxidant activity (Tor‐Roca et al., 2020; Yaermaimaiti et al., 2021). Fruit and vegetable color is considered a decisive factor in measuring market acceptance; brighter colors reflect greater biological activity (Zhang, Choe et al., 2022). In leguminous plants, genes related to chlorophyll synthesis or degradation are mainly involved in the color change of green pods, whereas the chlorophyll synthesis pathway of golden pods is blocked (Liu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%